Acute Gastric Dilatation in Anorexia Nervosa. Issue 5917 (1st June 1974) - Jennings, K. P.; Klidjian, A. M.
Abstract : Two patients with anorexia nervosa were treated on a general surgical unit for acute gastric dilatation. In both cases the dilatation rapidly followed an increase in the usual low dietary intake of the patients, and the ingestion of extra food may have initiated the acute episode. Conservative treatment with parenteral fluids, nasogastric intubation, and then a gradual return to a normal diet proved a satisfactory method of management. In one patient the anorexia itself was improved.